PEREMPUAN KINASIH’S SOLIDARITY AS POLICY ENTREPRENEURS: INNOVATIVE STRATEGIES IN SUPPORTING WOMEN FARMERS TOWARDS FOOD SOVEREIGNTY - Tevana Sari Dewi; Umi Qodarsasi (Jurnal Konstituen, 2024)
This research analyzes the contribution of the Solidaritas Perempuan (SP) Kinasih Yogyakarta community in encouraging the creation of gender-responsive public policies in the food sector. The method used in this research is descriptive qualitative, which examines various advocacy strategies that have been carried out by SP Kinasih, ranging from community organizing and public education to policy advocacy. The findings show that SP Kinasih has played an important role in influencing public policies at the local and national levels. However, the research also highlights the importance of building broader coalitions and strengthening the capacity of civil society organizations in facing complex challenges. Keywords: Women's Food Sovereignty, Advocacy Strategy, Public Policy